2008
DOI: 10.1002/cm.20270
|View full text |Cite
|
Sign up to set email alerts
|

Treponema denticola Msp‐deduced peptide conjugate, P34BSA, promotes RhoA‐dependent actin stress fiber formation independent of its internalization by fibroblasts

Abstract: P34(BSA), a BSA conjugate of a synthetic 10-mer peptide deduced from Treponema denticola major outer sheath protein (Msp), stabilizes actin filaments in fibroblasts and retards cell motility. We reported previously that it is internalized by cells, binds and bundles actin filaments in vitro, and activates RhoA; yet, its site and mechanism of action were not defined. We have assessed P34(BSA)'s modes of interaction with and signaling to fibroblasts. At 4 degrees C, P34(BSA) was not internalized, but it bound to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Cholesterol depletion by M␤CD suppressed the ability of P. gingivalis for intracellular persistence and cytokine induction in mouse macrophages (33) and abolished actin polymerization induced by P. gingivalis OM vesicles (32). Lipid raft-dependent internalization was also observed with Treponema denticola Mspdeduced peptide conjugate, P34BSA, which induced actin stress fiber formation through PI3K and RhoA activation, although lipid raft activation by P34BSA, but not lipid raft-dependent internalization, is linked to PI3K and RhoA activation (34).…”
Section: Discussionmentioning
confidence: 94%
“…Cholesterol depletion by M␤CD suppressed the ability of P. gingivalis for intracellular persistence and cytokine induction in mouse macrophages (33) and abolished actin polymerization induced by P. gingivalis OM vesicles (32). Lipid raft-dependent internalization was also observed with Treponema denticola Mspdeduced peptide conjugate, P34BSA, which induced actin stress fiber formation through PI3K and RhoA activation, although lipid raft activation by P34BSA, but not lipid raft-dependent internalization, is linked to PI3K and RhoA activation (34).…”
Section: Discussionmentioning
confidence: 94%
“…In the study, RhoA activation was determined by the RhoA G-LISA TM kit, the protocol has been validated by previous studies [17,18]. It can accurately and reproducibly measure the change of GTPbound RhoA in HBVSMCs.…”
Section: Molecule Mechanism Involved In the Inhibitory Effects Of Hl07mentioning
confidence: 99%
“…Studies by Ellen and coworkers have demonstrated that Msp disrupts the actin cytoskeleton of gingival fibroblasts, with specific effects, including disruption of actin stress fibers (45) and induction of de novo synthesis of subcortical actin filaments (35, 37, 46, 47). A specific peptide sequence within Msp has been shown to promote stress fiber formation (48, 49). Concurrently, and presumably related to this phenomenon, Msp blocks the ability of fibroblasts to regulate intracellular calcium gradients (50), which may contribute to the rather diverse range of morphological responses observed.…”
Section: Interactions With Host Cellsmentioning
confidence: 99%